Advanced Applications of Evolution processes in in Solutions of Interacting Polymers - Suleimenov, I. E.; Panchenko, S. V.; Sedlakova, Z.; Park, I. T. (Recent Contributions to Physics, 2015)
In this work the experimental technique, which allows investigate the processes of artificial evolution, is offered. Artificial evolution processes occur in solutions of polymers capable to form hydrophilic interpolymer associates. Those processes are caused by external action, for example, periodical heating of solution of interacting polymers. The observation of phase transition shows that evolution processes can be governed by external action in special way. Here we show the relationship of experiments that ensure artificial evolution in systems of the specified type in physical chemistry of polymers with processes in nanotechnology and processes in sociology and economic disciplines. Such approach is prevalent for systems having large number of elements and specified relations between its elements.